Textos escritos de alunos surdos e ouvintes sob o olhar da linguística textual - Alves, Sandra Maria de Lima (2012)
Language has been for a long time the main subject of human sciences study. Linguistics has shown that the work with language must overlap working with itself. The Portuguese teacher needs to be opened the several kinds of text production, as well as, to the different linguistics brought to classroom by the students. Grammar study needs to be in reading, writing and contextualized interpretation. So, the teacher chosen theory is to be clear to go into practice. The conservative teaching still hegemonic in our schools needs to be discussed and changed for its political function of forming citizens for the contemporary society and its complex demands and differences. Thus, this study aimed to describe and analyze texts for deaf and hearing students from this confrontation, extract the productions of the deaf, the research focus, and specific characteristics with regard to such phenomena as the stages of interlanguage and the various difficulties in writing which link to social conditions, affective and cognitive. The results showed that the deaf, despite the limitations of hearing, have all conditions to obtain proficiency in a second language. For this reason, the problems in language learning of those can and should be faced by the teacher with linguistically based methodologies and targeted to the particularities of that social group. To conduct this qualitative, descriptive research, we investigated the use of bilingual model to identify its limits and possibilities of working with written texts in six (06) deaf students and six (06)hearing students, seeking to compare their productions. By from this, we hope to contribute to demystify the idea that deaf people will not write in Portuguese satisfactorily because they are "only" users of LIBRAS.